Structure and magnetism of orthorhombic epitaxial FeMnAs - Demaille, Dominique (2013)
The molecular beam epitaxy growth of Fe on MnAs/GaAs(001) leads to the formation of an epitaxial FeMnAs phase at the Fe/MnAs interface. The investigation of the structure by high angle annular dark field imaging in a scanning transmission electron microscope reveals an unusual orthorhombic structure, with vacancy ordering. Ab initio calculations show an antiferromagnetic ground state for this orthorhombic FeMnAs.